SADRANAN TRADISI TERGERUS PANDEMI (STUDI KASUS : DESA KARANGGUDE KULON) - Jihan Kha Midah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2021)
Tradition is a legacy of the past that lives and is inherited in the midst of society, which contains a series of ideas and ideals of shared ideals and contains some rules about the ideals of coexistence in society.. Sadranan tradition is a cultural acculturation in the form of ancestral heresy and Islamic culture. Sadranan tradition is an Islamic tradition in Java. The term Javanese Islam in the context of this work is understood as a belief system and local worship that is different from the Islamic tradition in general.This tradition is carried out routinely once a year every year. However, after the outbreak of the covid 19 virus pandemic in Indonesia, which began to be widely discussed starting in 2020. Impact on community activities that collect a lot of time began to be reduced and even banned, sesai with government kebikalan in order to prevent the spread of the virus. One of the policies issued by the government is the existence of PSBB. The global pandemic that struck not only from the economic field but in the social and cultural sectors and other fields. Apart from government policy factors that caused the erosion of sadranan traditions in Karanggude Kulon village, there are also factors from people who are afraid of the dangers of the corona virus.